The Effect of Gurdi Process Prameter and Fiber Variation On The Delamination of Banana Stem Fiber Composites - Supendi Supendi; Bambang Dwi Haripriadi; Siti Umira (International Journal of Science and Environment (IJSE), 2026)
Delamination is one of the main defects that often occur in the process of curving composite materials and can degrade the quality of the hole as well as the integrity of the joint structure. Banana stem fiber-reinforced thermoplastic composites have the potential to be an environmentally friendly material, but they are still susceptible to delamination due to the influence of the processing process parameters and variations in fiber composition. This study aims to analyze the influence of drill bit diameter, feed rate, drill bit tip angle, fiber arrangement, and cooling medium on delamination at the entrance and exit sides of the banana stem fiber composite hole. The research method used was an experiment with the design of the Taguchi Orthogonal Array L27, while the data analysis was carried out using Signal-to-Noise Ratio (S/N Ratio) with characteristics of Smaller-The-Better and Analysis of Variance (ANOVA) at a constant spindle rotation of 500 rpm. The results showed that the addition of banana stem fiber was able to increase the tensile strength of composites by 61.7% compared to pure thermoplastics. ANOVA analysis showed that on the inlet side delamination, the drill bit diameter, feeding motion, and cooling medium had a significant effect, while on the exit side, the drill bit diameter and drill bit tip angle were the most dominant parameters. Overall, the drill bit diameter is the factor that has the greatest influence on minimizing delamination so that it is the main parameter that needs to be optimized to improve the quality of the hole from the drill in the thermoplastic composite reinforced with banana stem fiber.